A cytokine receptor–targeting chimera toolbox for expanding extracellular targeted protein degradation - Kaan Kumru; Zi Yao; Brandon B. Holmes; Fangzhu Zhao; Yun Zhang; Emilio Ferrara; Trenton M. Peters-Clarke; Kevin K. Leung; James A. Wells (Proceedings of the National Academy of Sciences, 2026)
Extracellular targeted protein degradation (eTPD) is an important new modality for manipulating the extracellular proteome. However, most eTPD receptors are expressed broadly or are restricted to the liver, limiting specific degradation in other tissues. Cytokine receptor–targeting chimeras (kineTACs) are genetically encoded bispecifics for eTPD that fuse a natural ligand like CXCL12 to an antibody, directing soluble or membrane proteins for lysosomal degradation using the widely expressed chemokine receptor CXCR7 (K. Pance et al. , Nat. Biotechnol. 41 , 273–281 (2023)]. Here, we dramatically expand the kineTAC toolbox by constructing 81 different kineTACs based on an unbiased list of cytokines, chemokines, and growth factors. Remarkably, 55 of these expressed at suitable levels for analysis without any optimization. Many of these kineTACs bind receptors that have unique cell-type expression profiles, allowing for eTPD in specific cells and tissues, and some were more potent than the original CXCL12-based kineTAC against specific targets. We further show the internalizing capability of a kineTAC can enhance the performance of antibody drug conjugates. We believe these simple, genetically encoded tools will be useful for expanding the applications for optimized or cell type–selective eTPD.